Wiggsy Sivertsen posing with two women - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows Wiggsy Sivertsen, (far left), posing with two unidentified women. The woman on the right has a button that reads: "No on prop 64 LaRouche Initiative".